2020
DOI: 10.1111/jch.13958
|View full text |Cite
|
Sign up to set email alerts
|

Further evidence that methods based on spot urine samples should not be used to examine sodium‐disease relationships from the Science of Salt: A regularly updated systematic review of salt and health outcomes (November 2018 to August 2019)

Abstract: The aim of this eighth Science of Salt outcomes review is to identify, summarize, and critically appraise studies on dietary sodium and health outcomes published between November 1, 2018, and August 31, 2019, to extend this series published in the Journal since 2016. The standardized Science of Salt search strategy was conducted. Studies were screened based on a priori defined criteria to identify publications eligible for detailed critical appraisal. The search strategy resulted in 2621 citations with 27 stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 61 publications
1
4
0
Order By: Relevance
“…Consistent with previous Science of Salt reviews, we found that most RCTs were short-term (≤1month) and assessed intermediate health outcomes (BP) [ 72 80 ]. Here, there were no long-term RCTs examining Category I (Mortality) or Category II (Morbidity) outcomes which are considered as being more important to patients.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Consistent with previous Science of Salt reviews, we found that most RCTs were short-term (≤1month) and assessed intermediate health outcomes (BP) [ 72 80 ]. Here, there were no long-term RCTs examining Category I (Mortality) or Category II (Morbidity) outcomes which are considered as being more important to patients.…”
Section: Discussionsupporting
confidence: 82%
“…In the series of Science of Salt health outcomes reviews [ 72 80 ], this is the first to have identified physical performance as a health outcome. This is a valuable addition to the scope of adverse health outcomes relating to high sodium intake as it addresses an important quality of life indicator.…”
Section: Discussionmentioning
confidence: 99%
“…Estimated 24-h urinary Na was associated with a J-shaped curve for blood pressure and mortality, whereas measured 24-h urinary sodium was linearly associated with mortality. A policy statement from the World Hypertension League issued in 2019 cautions against the use of spot urines and urges rigorous study of spot urines based on systematic review of Na–disease association studies published November 2018–August 2019 ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…The first line of HTN prevention and treatment is lifestyle/nonpharmacological interventions: weight loss, healthy dietary patterns (Dietary Approaches to Stop HTN and Mediterranean diets), sodium reduction, increased potassium, physical activity, stress reduction, smoke avoidance, and limiting indoor air pollution [8–12].…”
Section: Therapeutic Lifestyle/nonpharmacological Interventionsmentioning
confidence: 99%